2022
DOI: 10.1097/md.0000000000030717
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting reversible contraceptives utilization and its determinants among married Yemeni women of childbearing age who no longer want children

Abstract: Some contraceptive methods, such as long-acting and permanent methods, are more effective than others in preventing conception and are key predictors of fertility in a community. This study aimed to determine which factors were linked to married women of childbearing age who no longer desired children using long-acting reversible contraceptives (LARCs) in Yemen. We used a population-based secondary dataset from Yemen's National Health and Demographic Survey (YNHDS), conducted in 2013. The study analyzed a weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The findings also show that women who had attained primary school education had higher odds of using modern contraceptives than their uneducated counterparts. This finding is consistent with previous studies that have shown a similar pattern of relationship between educational status and contraceptive use [5,9,16]. Education empowers women to have autonomy in making important decisions regarding fertility related issues and help them exercise reproductive health rights compared to uneducated women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings also show that women who had attained primary school education had higher odds of using modern contraceptives than their uneducated counterparts. This finding is consistent with previous studies that have shown a similar pattern of relationship between educational status and contraceptive use [5,9,16]. Education empowers women to have autonomy in making important decisions regarding fertility related issues and help them exercise reproductive health rights compared to uneducated women.…”
Section: Discussionsupporting
confidence: 92%
“…In countries with high fertility rates, promoting contraceptives averts 32% of all maternal deaths and approximately 10% of child mortality. Modern contraceptives also make a huge contribution to the achievement of universal primary schooling, female empowerment, and reducing poverty and hunger [5]. Family planning is also important in preventing unintended pregnancies and unsafe abortions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Boah et al 20 and Ebrahim et al 21 have shown that the acceptance and use of LARC in rural areas was lower compared with urban areas, which represents a finding similar to that of the present study. In less developed settings or settings with less potential for development, reproductive health care is directly linked to the culture of the setting.…”
Section: Discussionsupporting
confidence: 91%
“…According to the guidance of reviewed literature4 36–43 and the availability of the variables in BDHS 2017–2018, several explanatory variables were included in this current analysis. They are the age of women, education of women, employment status of women, husband/partner’s education, religion, body mass index (BMI), media exposure, current breastfeeding status, parity, birth history in last 5 years, history of a terminated pregnancy, hearing information about FP from media, the decision for using contraception, knowledge of ovulatory cycle, women decision-making power, household wealth status, place of residence and administrative division.…”
Section: Methodsmentioning
confidence: 99%